Antioxidant and antibacterial activities of ruta angustifolia extract - Shuib, Nur Azra; Sulaiman, Fatimatul Akmal; Razak , Izzatie; Darnis, Deny Susanti (Universiti Teknologi Malaysia, 2015)
Ruta angustifolia was used in this study in order to evaluate the antimicrobial activity and antioxidant properties and its correlation with the polyphenolic content. Two Gram-positive bacteria (Staphylococcus aureus ATCC 25923, Bacillus cereus ATCC 11778) and two Gram–negative bacteria (Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 8739) were used to determine the antibacterial activity. Aqueous maceration extract was used for antioxidant activities and methanolic maceration extract was used for antibacterial activity. The antioxidant properties and activities were evaluated by using total phenolic content (TPC), total flavonoid content (TFC), DPPH free radical scavenging activity and beta-carotene bleaching method. Whereas, the antibacterial activity was examined using disc diffusion method against selected microorganism at concentration 1.0 mg/disc. The results showed the phenolic content of R. angustifolia extract was 18.89 g GAE/100 g extract while the flavonoid content was 14.170 g QE/100 g extract. R. angustifolia exhibited good radical scavenging with IC50 value of 2.04 mg/ml. The result for disc diffusion method showed no inhibition zone against all the strains of bacteria at 1.0 mg/disc concentration of the extract. Based on the results, it can be concluded that the R. angustifolia aqueous extract has the antioxidant properties and there is correlation between polyphenolic content of the extract with its antioxidant activity. However, R. angustifolia methanolic extract did not show any antibacterial activity.